Faktor-faktor yang Berhubungan dengan Kunjungan Kelas Ibu Hamil - Megawati Megawati (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Program class pregnant women is one of prenatal education can increase knowledge of the mother. Based on the achievement of national targets coverage class visit pregnant women should reach 95,26% while data from pemali primary health center reach 50,96% the amount is still less than the target of national coverage. the research design used by researchers is deskriptif analytical survey method using a cross-sectional. In this research the variables used were the dependent variables (dependen) is classroom visits for pregnant women. Free independent variables are the level of knowledge, education, employment and parity. approach is a research study dynamics of the correlation between variables where the population is taken all pregnant women in the area occupational pemali public health center in 2014 as many as 673 peoples and with 96 peoples samples. Based on these results suggestions that I raise is the need For more efforts from health professional to provide health promotion of pregnant women class.